Nieuczciwa reklama jako przykład czynu nieuczciwej konkurencji - Sieradzka, Małgorzata (Wydawnictwo Uniwersytetu Wrocławskiego, 2007)
Competition is an invention of the West. Deriving profits from it is possible only then when competition is fair. Effective protection against unfair actions that hit in the mechanism of the competition is ensured by lawful means which allow to eliminate them. The regulations of the act on opposing unfair competition are applied. They protect interests of entrepreneurs and clients who are exposed to the acts of unfair competition. The most dangerous act of unfair competition is unfair advertising. Its role in economy is very significant. Competition enforces entrepreneurs to do various activities which are aimed at gaining clients. The instrument that facilitates the goal is advertising. The entrepreneurs do not always use fair advertising allowed by the law and common customs. That is why legislation laid down a number of regulations that contribute to opposing unfair competition (including advertising), simultaneously protecting not only consumers but also other participants of economical conduct.
Keywords: nieuczciwa reklama; nieuczciwa konkurencja